2006
DOI: 10.1016/j.jfludis.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceptual and conceptual similarity in lexical priming of young children who stutter: Preliminary findings

Abstract: The purpose of this study was to investigate the influence of conceptual and perceptual properties of words on the speed and accuracy of lexical retrieval of children who do (CWS) and do not stutter (CWNS) during a picture-naming task. Participants consisted of 13 3-to 5-year-old CWS and the same number of CWNS. All participants had speech, language, and hearing development within normal limits, with the exception of stuttering for CWS. Both talker groups participated in a picturenaming task where they named, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 40 publications
(54 reference statements)
7
36
1
4
Order By: Relevance
“…Nevertheless, it seems relatively safe to say that semanticphonological connections are probably not a major source of difficulty for CWS. Rather, any difficulties CWS have with speech-language production may be more related to lexical or phonological encoding (e.g., Byrd et al, 2007;Hartfield & Conture, 2006), morphosyntactic construction (e.g., Anderson & Conture, 2004), or a combination of processes (Anderson, 2007;Anderson & Byrd, in press). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it seems relatively safe to say that semanticphonological connections are probably not a major source of difficulty for CWS. Rather, any difficulties CWS have with speech-language production may be more related to lexical or phonological encoding (e.g., Byrd et al, 2007;Hartfield & Conture, 2006), morphosyntactic construction (e.g., Anderson & Conture, 2004), or a combination of processes (Anderson, 2007;Anderson & Byrd, in press). …”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hartfield and Conture (2006) examined the effect of conceptual (i.e., categorical and functional) and perceptual (i.e., physical) primes on picture naming speed and accuracy. Findings revealed that CWS were not only slower to name pictures across all conditions than CWNS, but they also named pictures more rapidly following functionally related primes relative to physically related primes.…”
Section: Lexical Processing In Children Who Stuttermentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Some other recent empirical studies on children who stutter (CWS) [5][6][7][8][9][10][11][12][13] suggest that linguistic issues in CWS may be somewhat different from children who do not stutter (CWNS). Arguably, further investigation in this area of research should provide specifically meaningful insight into whether some parts of the linguistic processes are involved in the initiation and maintenance of stuttering in young children.…”
mentioning
confidence: 99%
“…Nesta pesquisa, observa-se maior uso do acessório externo fornecido com o pacote de software 9,[13][14][15]18,30 , mas o teclado veio em segundo lugar [10][11][12]17 . Somente o estudo de Finlayson, King e Blundell 16 utilizou um mouse para registro das respostas.…”
Section: Discussionunclassified